Noninvasive Quantification of Pancreatic Fat in Humans - Lingvay, Ildiko (The Endocrine Society, 2009)
Objective: To validate magnetic resonance spectroscopy (MRS) as a tool for non-invasive quantification of pancreatic triglyceride (TG) content and to measure the pancreatic TG content in a diverse human population with a wide range of body mass index (BMI) and glucose control. Methods: To validate the MRS method, we measured TG content in the pancreatic tissue of 12 lean and 12 fatty ZDF rats (ages 5–14 weeks) both by MRS and the gold standard biochemical assay. We used MRS to measure pancreatic TG content in vivo in 79 human volunteers. Additionally, to assess the reproducibility of the method, in 33 volunteers we obtained duplicate MRS measurements 1–2 weeks apart. Results: MRS quantifies pancreatic TG content with high reproducibility and concordance to the biochemical measurement (Spearman’s rank correlation coefficient = 0.91). In humans, median pancreatic TG content was as follows: (1) normal weight and normoglycemic group 0.46 f/w%, (2) overweight or obese but normoglycemic group 3.16 f/w%, (3) impaired fasting glucose or impaired glucose tolerance group (BMI matched with group 2) 5.64 f/w%, and (4) untreated type 2 diabetes group (BMI matched with group 2) 5.54 f/w% (Jonckheere-Terpstra trend test across groups p < 0.001). Conclusions: Human pancreatic steatosis, as measured by MRS, increases with BMI and with impaired glycemia. MRS is a quantitative and reproducible non-invasive clinical research tool which will enable systematic studies of the relationship between ectopic fat accumulation in the pancreas and development of type 2 diabetes.